Diagnosis of Deep-vein Thrombosis with an Ultrasonic Doppler Technique. Issue 5660 (28th June 1969) - Evans, D. S.; Cockett, F. B.
Abstract : An ultrasonic technique has been used to diagnose deep-vein thrombosis, the venous system being examined from the calf to the inferior vena cava. The method is quick, simple, and repeatable, and the results compare favourably with those from phlebography.